Implementation of Land Acquisition Policy in The Perspective of Social Justice For Indigenous Peoples in Sorong City - Ludia Baransano; Karmanis Karmanis; Tri Lestari Hadiati (Law and Justice research journal, 2026)
This research aims to analyze the implementation of land acquisition policies in Sorong City from the perspective of social justice for indigenous peoples, and to evaluate the extent to which customary rights are accommodated in the development process. The research method is a mixed-methods study with an embedded design. The qualitative approach was the primary instrument, using in-depth interviews with five key speakers, including land authorities and representatives of the Malaloi Indigenous Peoples Institution (LMA). Quantitative approaches are used only in correlation analysis to reinforce qualitative findings. The study's results show a "Paradox of Justice" in Sorong City. Procedurally, the land acquisition policy has been effective in accordance with Law Number 2 of 2012, supported by a strong statistical correlation between land acquisition and social justice. However, substantively, justice for indigenous peoples has not been fully achieved because the involvement of indigenous leaders in deliberations is often considered a mere administrative formality. The highest correlation between indigenous peoples and social justice confirms that the recognition of customary rights is the main determinant of justice in public policy. The main obstacles identified include difficulties in the administrative documentation of customary lands and paradigmatic differences between the government's materialistic values and the sociocultural values of indigenous peoples. The theoretical implications of this study confirm the importance of communication factors and the disposition of implementers in the implementation of policies in customary territories. In practice, the government needs to reformulate deliberations based on local values and the structural recognition of customary rights.